The efficacy and safety of IL-13 inhibitors in atopic dermatitis: A systematic review and meta-analysis - Zhang, Yan; Jing, Danrong; Cheng, Jun; Chen, Xiang; Shen, Minxue; Liu, Hong (Frontiers in Immunology, 2022)
Background Several clinical trials have evaluated the efficacy and safety of interleukin-13 (IL-13) with lebrikizumab and tralokinumab in patients with moderate to severe atopic dermatitis (AD). However, the safety and efficacy of IL-13 inhibitors as a potent biologic for AD remain elusive. Objective To assess the efficacy and safety of IL-13 inhibitors in moderate to severe AD. Method Randomized clinical trials (RCTs), comparing IL-13 inhibitors vs placebo treatment in patients with moderate to severe AD, were identified from public database from its inception to November 9th, 2021. The study was registered in PROSPERO (CRD42021254920). Results Six studies reporting 7 RCTs involving 2946 patients with moderate-to-severe AD were included for the pooled analysis. Compared with placebo, antagonizing IL-13 with lebrikizumab and tralokinumab showed a greater improvement in percentage change of EASI (MD -20.37, 95%CI -32.28, -8.47), and a larger proportion of patients achieving numerical rating scale (NRS) with more than 4-points improvement (RR 1.59, 95%CI 1.23, 2.05). Additionally, IL-13 inhibitors also improved impaired dermatology life quality index (DLQI) (MD -14.49, 95%CI -19.23, -9.75). In terms of safety, both lebrikizumab and tralokinumab were well tolerated, with the except that they were linked to an increased risk of conjunctivitis compared to placebo treatment. Conclusion Antagonizing IL-13 with lebrikizumab and tralokinumab have demonstrated encouraging clinical efficacy against moderate-to-severe AD with excellent safety profile, albeit they did come with a higher risk of conjunctivitis than placebo treatment.